Winning the long war retaking the offensive against radical Islam - Berman, Ilan (Rowman & Littlefield Publishers, 2009)
Middle East expert Ilan Berman offers new thinking on counterterrorism strategy and provides the new administration with ways to close the gaps in current American counterterrorism strategy. --from publisher description.